E-WIN Project 2016: Evaluating the Current Gender Situation in Neurosurgery Across Europe-An Interactive, Multiple-Level Survey - Steklacova, Anna; Bradac, Ondrej; de Lacy, Patricia; Benes, Vladimir (World neurosurgery, 2017)
BACKGROUND: The proportion of women among neurosurgeons appears to be growing worldwide with time. Official data concerning the current situation across Europe have not yet been published. Thus, there are still concerns about gender inequality. The European Women in Neurosurgery Project 2016 was designed to recognize the current situation across Europe. METHODS: The office holders of the national neurosurgical societies of 39 countries forming the European Association of Neurosurgical Societies were contacted to provide data stating the proportion of women in neurosurgery. Obtained data were supplied with the results of an online survey. RESULTS: The response rate of national office holders was 90%. The number of reported neurosurgeons was 12,985, and overall proportion of women represented was 12%. Two hundred thirty-seven responses to online questionnaire were taken into account. The overall proportion of female respondents was 30%. There was no intergender variability in responses regarding amount of working time per week, exposure to surgeries, or administrative work. Male respondents reported dedicating significantly more time to scientific work and feeling more confident dictating own career direction. Female respondents reported being less often married, having fewer children, a stronger perception of gender significance level, and a higher appreciation of personal qualities. CONCLUSIONS: Neurosurgery is a challenging field of medicine. The results of our survey did not imply an overall feeling of gender inequality among European respondents, although women believe that the gender issue to be more important than men do and that they have to sacrifice more of their personal lives.
Keywords: neurochirurgie; Male; Physicians, Women; Europe; Adult; rozložení podle pohlaví; dospělí; mužské pohlaví; Marital Status; Sex Distribution; Evropa; Sexism; postoj zdravotnického personálu; lékařky; Neurosurgeons; lidé; Attitude of Health Personnel; ženské pohlaví; Humans; Neurosurgery; manželský stav; neurochirurgové; Female; lidé středního věku; sexismus; Middle Aged